The relationship between team characteristics and team effectiveness : an integration of Campion's and Cohen's models : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University, Albany, New Zealand - Little, Kerri M. (Massey University, 1997)
This study uses 22 teams from 3 organisations to examine the influence of team characteristics on the effectiveness of work teams. The model tested is an integration of Cohen's (1994) and Campion, Medsker, and Higgs' (1993) models. Five independent characteristics are used: task design, interdependencies, composition, context, and process. These are examined along with four effectiveness criteria: perceived performance, quality of work life, managers' judgements of performance, and withdrawal behaviour. The results of a path analysis show that task design and process characteristics predict team members' ratings of performance and quality of work life while interdependence and composition characteristics predict only team members' ratings of performance. As hypothesised, team members' quality of work life negatively predicts their withdrawal behaviour.